Integrated weed management in Kansas winter wheat - Refsell, Dawn E. (Kansas State University, 2013)
Integrated weed management (IWM) is an ecological approach to weed control that reduces dependence on herbicides through understanding of weed biology and involves using multiple weed control measures including cultural, chemical, mechanical and biological methods. The critical period of weed control is the duration of the crop life cycle in which it must be kept weed-free to prevent yield loss from weed interference. Eight experiments were conducted throughout Kansas between October 2010 and June 2012 to identify this period in winter wheat grown under dryland and irrigated conditions. Impact of henbit and downy brome density on winter wheat yields were evaluated on four farmer’s fields with natural populations and on a research station with overseeded populations. Henbit density up to 156 plants m-2 did not affect winter wheat yield, while downy brome at a density of 40 plants m-2 reduced yield by 33 and 13% in 2011 and 2012, respectively. In the presence of downy brome, winter wheat should be kept weed-free approximately 30 to 45 days after planting to prevent yield loss; otherwise, weeds need to be removed immediately following release from winter dormancy to prevent yield loss due to existing weed populations. Flumioxazin and pyroxasulfone are herbicides registered for use in winter wheat, soybean and corn for control of broadleaf and grass weeds. Flumioxazin and pyroxasulfone were evaluated for plant response to localized herbicide exposure to roots, shoots, or both roots and shoots utilizing a novel technique. Two weed species, ivyleaf morningglory and shattercane, as well as two crops, wheat and soybean, were evaluated for injury after localized exposures. The location and expression of symptoms from the flumioxazin and pyroxasulfone herbicides were determined to be the shoot of seedling plants. The utilization of preemergence herbicides in winter wheat is not a common practice, although application may protect winter wheat from early season yield losses as determined by the critical weed-free period. Kansas wheat growers should evaluate the presence and density of weed species to determine which weed management strategy is most advantageous to preserving winter wheat yield.
Keywords: Critical period of weed control; Pyroxasulfone; Flumioxazin; Downy brome; Henbit; Weed interference; Agriculture, General (0473); Agronomy (0285)